2009
DOI: 10.1038/cmi.2009.4
|View full text |Cite
|
Sign up to set email alerts
|

Cloning and Characterization of DULP, a Novel Ubiquitin-Like Molecule from Human Dendritic Cells

Abstract: We identified a novel ubiquitin-like molecule DULP from human dendritic cells. DULP contains a domain that shares 26% identity and 34% similarity with ubiquitin, and it possesses the corresponding Ile-44 hydrophobic patch used by mono-or poly-ubiquitin to interact with a ubiquitin-interaction motif (UIM) or ubiquitin-associated domain (UBA). Lysine residue corresponding to 6 of ubiquitin, which is involved in the formation of a multi-ubiquitin chain that can bind proteasomal subunit Rpn10/S5a, is also conserve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 130 publications
0
6
0
Order By: Relevance
“…The complete comprehension of how these events are regulated is crucial for the identification of those defects responsible for the development of many diseases, from inflammatory diseases to cancer. Our previous reports showed that the protein HOPS plays a central role in different cellular functions, including maintenance of genomic stability, correct proliferation and progression through the cell cycle 1 , 10 , 14 , 28 , 29 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The complete comprehension of how these events are regulated is crucial for the identification of those defects responsible for the development of many diseases, from inflammatory diseases to cancer. Our previous reports showed that the protein HOPS plays a central role in different cellular functions, including maintenance of genomic stability, correct proliferation and progression through the cell cycle 1 , 10 , 14 , 28 , 29 .…”
Section: Discussionmentioning
confidence: 99%
“…Instead, IL-6 could be responsible of the increased expression of HOPS during liver regeneration, possibly through a mechanism involving the binding of the transcription factor C/EBPβ to the promoter of HOPS and the activation of its transcription 8 , 9 . HOPS has a role in mitotic spindle assembly and centrosome duplication and is involved in the control of cell cycle progression 10 12 . Moreover, it was found to participate in the ERAD pathway, where it plays an important role in the control of sterol-accelerated ubiquitination and degradation of the cholesterol biosynthetic enzyme HMG-CoA reductase 13 .…”
Section: Introductionmentioning
confidence: 99%
“…In 2009, Liu et al. 7 mentioned that Tmub1 can induce apoptosis in 293T cells, but the specific role and the underlying mechanisms are yet to be revealed. In our preliminary studies, we found that Tmub1 may interact with an apoptosis-related protein, p63, indicating a possible relationship between Tmub1, p63, and apoptosis.…”
Section: Introductionmentioning
confidence: 99%
“…Tmub1 encodes for a protein, HOPS/DULP, containing transmembrane domains and a ubiquitin-like domain (UBL) [1] , [2] . Ubiquitin can be employed to modify proteins by either single or multiple ubiquitin conjugation to mark them for proteasomal destruction, endocytosis and binding to other proteins [3] [5] .…”
Section: Introductionmentioning
confidence: 99%